2016
DOI: 10.1016/j.jfda.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic activity of Allium chinense bulbs

Abstract: Allium chinense is a medicinal plant and nutritional food commonly used in Eastern Asia. In this study, we investigated the in vitro antioxidant activity (scavenging of α,α-diphenyl-β-picrylhydrazyl free radical, total phenol content, reducing power, and total antioxidant activity) and constituents of various extracts from A. chinense. Moreover, we also studied the in vivo hypolipidemic effects of extracts on high-fat-diet Wistar rats. Ethanol extracts from A. chinense showed notable antioxidant activity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…The low or negligible antioxidant capacity in the hexane leaf and bulb extract may be due to the low content of phenol [19] and flavonoid [20]. Our findings correlate with the previous report by Lin in A. chinense bulb [25].…”
Section: Discussionsupporting
confidence: 91%
“…The low or negligible antioxidant capacity in the hexane leaf and bulb extract may be due to the low content of phenol [19] and flavonoid [20]. Our findings correlate with the previous report by Lin in A. chinense bulb [25].…”
Section: Discussionsupporting
confidence: 91%
“…The presence of these elements is related to the formation of calcium phosphate phases. 35 There are also elements such as carbon, oxygen, sodium, aluminum, chlorine, and magnesium, which are part of SBF preparation. As it is well known, Martel et al, not only the calcium ions promote the apatite formation but also other elements such as chlorine, silicon, aluminum, and sulfur in the system are consumed forming carbonated apatite that enhances the rapid formation of the biological apatite evidenced by the Ca/P ratio (previously mentioned) obtained in the scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…Various mechanisms including evoking the insulin production and secretion, influencing gene expression of glucose-regulating enzymes, inhibiting cholesterol absorption, inhibiting hepatic cholesterol biosynthesis, increasing cholesterol turnover, inhibiting development of arteriosclerotic plaques in arterial walls, anticoagulant, and fibrinolytic effects may contribute in these cardio-protective activities of Allium plants ( 26 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The major bioactive constituents found in Allium plants including saponins such as alloside B, polyphenols, and flavonoids such as quercetin and organo-sulphur compounds such as allicin are recognized as responsible agents for their beneficial cardiovascular effects ( 25 26 ). Our previous studies have shown the strong hypoglycemic, antioxidant, and fibrinolytic activities for A. elburzense extract which may participate in its preventive effects on atherosclerosis ( 8 9 ).…”
Section: Discussionmentioning
confidence: 99%